Typologizing nominal expressions: the noun phrase and beyond - Louagie Dana; Reinöhl Uta (Linguistics, 2022)
This article develops foundations for a new typology of nominal expressions. Despite the significant diversity attested in languages around the world, a view traditionally and sometimes still found holds that languages either have ‘classic’, rigidly structured noun phrases (NPs) or lack them. A simple dichotomy, however, does not adequately represent the significant language-internal and crosslinguistic diversity of forms and functions of nominal expressions. While many linguists may not in fact think in such binary terms, a comprehensive typology is still wanting. This article offers foundations towards such a typology, with a particular emphasis on language-internal diversity. This diversity within languages has received little attention in previous studies, even while it reveals much about the actual complexity in the nominal domain. Besides surveying structural types and their motivating factors across as well as within languages from around the world, this article approaches nominal expressions also from a variety of other perspectives to enrich our understanding of them. This includes approaching nominal expressions from the perspective of word class systems as well as diachronically. We round off the article by looking at the impact of orality-literacy dimensions and communicative modes.